Elucidating the impact of soil’s physico-chemical properties and seasonal variation on earthworm distribution in flood-prone areas of Harike wetland, India - Ankeet Bhagat; Madan Lal; Anu Bala Chowdhary; Vinod Kumar; Shakoor Ahmed; Amandeep Kaur; Arvinder Kaur (Scientific Reports)
Abstract This study highlights the interplay between soil’s physico-chemical characteristics, seasons, anthropogenic interference (agricultural practices) and flooding in shaping the earthworm population. Two disturbed (agricultural: MV and KQK) and two undisturbed (protected: HK1 and HK2), flood prone sites of Harike wetland were sampled during spring, summer, monsoon, autumn and winter seasons of 2022. Out of all the sites, lowest population at HK1 (10.95% of the total) during the year highlights the critical influence of soil’s physico-chemical characteristics on earthworms. The sites with more area under monsoon floods had lower earthworm biomass during Autumn and Winter. Six species (5 exotic, 1 indigenous) were recorded from the wetland, Metaphire posthuma was most abundant and Amynthas robustus was least abundant (appeared at HK1 during winter in formers absence). The disturbed sites had higher abundance but lower diversity throughout the year. M. posthuma and Perionyx excavatus were observed to be tolerant to disturbance while A. corticis, A. robustus and Bimastos parvus were exclusive to undisturbed sites. Earthworm abundance was maximum (171 worms) during monsoon (favourable range of physico-chemical characteristics) and lowest during winter (24 worms). Values of Shannon-Wiener Index, Simpson’s Diversity Index and Species Evenness Index were also highest during monsoon. Interplay of stressors shaped the earthworm population, which was positively correlated (r = 0.027 to 0.887) with soil’s pH, potassium, organic matter, phosphorus, total nitrogen, moisture, organic carbon, and clay content. However, it was negatively correlated (r=-0.329 to -0.808) with zinc, lead, manganese, iron, copper, and electrical conductivity (further substantiated by PCA and Pearson’s coefficient of correlation).